Reliability and Validity of a Chinese Version of the Lysholm Score and Tegner Activity Scale for Knee Arthroplasty - Hongshi Huang; Si Zhang; Yi Wang; Yelverton Tegner; Yongjian Wang; Yanfang Jiang; Yingfang AO (Medical Journals Sweden, 2022)
Objective: To verify the reliability and validity of Chinese versions of the Lysholm score and the Tegner activity scale for knee arthroplasty. Methods: Sixty-four patients undergoing total knee arthroplasty and 28 healthy volunteers were included in this study. Participants were divided into 4 groups: a pre-operation group; a 3 months post-operation group; a 1-year post-operation group; and a control group of healthy volunteers. Participants completed the Lysholm score and Tegner activity scale twice over a period of 3-7 days. Results: The intraclass correlation coefficients of the Lysholm score and Tegner scale were both relatively high, at 0.99 and 0.97, respectively. Moreover, the Cronbach's alpha of the Lysholm score was 0.71. The items "locking" and "instability" differed slightly between groups (Kruskal-Wallis: for locking, χ2 (p) = 13.48, p = 0.0037; for instability, χ2 (p) = 4.32, p = 0.2292). Conclusion: The simplified-Chinese versions of the Lysholm score and the Tegner scale are applicable for use with patients undergoing total knee arthroplasty, and have relatively high validity and reliability. The items "locking" and "instability" should be combined with clinical data to make the Lysholm score more suitable for assessment of total knee arthroplasty. LAY ABSTRACT The aim of this study was to verify the reliability and validity of Chinese versions of the Lysholm score and the Tegner activity scale for assessment of knee arthroplasty. A total of 64 patients undergoing total knee arthroplasty (TKA) and 28 healthy volunteers were included in the study. Participants were divided into 4 groups: a pre-operation group; a 3 months post-operation group; a 1-year post-operation group; and a control group of healthy volunteers. Study participants completed the Lysholm score and Tegner activity scale score twice for over a period of 3-7 days, and the results analysed. The simplified-Chinese versions of the Lysholm score and the Tegner scale were found to be applicable for use with total knee arthroplasty patients, and to have relatively high validity and reliability. Furthermore, the items "locking" and "instability" should be combined with clinical data to make the Lysholm score more suitable for assessment of total knee arthroplasty.